Examining the effect of direct-from-blood bacterial testing on antibiotic administration and clinical outcomes: a protocol and statistical analysis plan for a pragmatic randomised trial - Li Wang; Wesley H Self; Todd W Rice; Matthew W Semler; Karen F Miller; Cheryl L Gatto; Andrea Fletcher; Romney M Humphries; Joanna L Stollings; Adrienne Baughman; Jakea Johnson; Edward T Qian; et al. (BMJ Open)
Introduction Patients with suspected bacterial infection frequently receive empiric, broad-spectrum antibiotics prior to pathogen identification due to the time required for bacteria to grow in culture. Direct-from-blood diagnostics identifying the presence or absence of bacteria and/or resistance genes from whole blood samples within hours of collection could enable earlier antibiotic optimisation for patients suspected to have bacterial infections. However, few randomised trials have evaluated the effect of using direct-from-blood bacterial testing on antibiotic administration and clinical outcomes. This manuscript describes the protocol and statistical analysis plan for a randomised trial designed to evaluate the effect of blood cultures plus direct-from-blood bacterial testing results compared with blood culture results alone on antibiotic administration and clinical outcomes.Methods and analysis We are conducting a prospective, single-centre, parallel-group, non-blinded, pragmatic, randomised trial. The trial will enrol 500 adult patients presenting to the emergency department at Vanderbilt University Medical Center with suspected bacterial infection who have been initiated on empiric intravenous vancomycin. Eligible patients are randomised 1:1 to receive Food and Drug Administration-approved direct-from-blood bacterial testing in addition to blood cultures or blood cultures alone. The primary outcome is the time to the last dose of intravenous vancomycin within 14 days of randomisation. The secondary outcome is the time to the last dose of systemic antipseudomonal beta-lactam antibiotics within 14 days of randomisation. Additional outcomes include highest stage of acute kidney injury, lowest platelet count and receipt of kidney replacement therapy within 14 days of randomisation, as well as hospital-free days, intensive care unit-free-days and all-cause, in-hospital mortality within 28 days of randomisation. Enrolment began on 13 December 2023.Ethics and dissemination The trial involves human participants and was approved by the Vanderbilt University Medical Center institutional review board with a waiver of informed consent (IRB#231229). Results will be submitted in a peer-reviewed journal and presented at scientific conferences.Trial registration number NCT06069206.